Bioremediation of Hydrocarbon Contaminated Soil: Assessment of Compost Manure and Organic Soap - Uguru, Hilary; O. I., Akpokodje (Transactions on Engineering and Computing Sciences, 2019)
This study was carried out to investigate the effect of compost manure and organic soap on hydrocarbon degradation in petroleum products contaminated soil. 10 kg of top soil collected at a depth of 0-20 cm, air dried and sieved, were poured into plastic containers. The soil samples were was pounded with 1 L of spent engine oil, 1 L of kerosene, 1 L of petrol and 1 L of diesel daily for five days. The containers were placed under natural environmental conditions for three weeks to enable full acclimatization of the petroleum products with the soil. A completely randomized design comprising T1 (Polluted soil without treatment ‘control’); T2 (10 kg contaminated soil + 500 g organic soap); T3 (10 kg contaminated soil + 500 g compost manure); and T4 (10 kg contaminated soil + 500 g compost manure + 500 g organic soap) was used for this study. Some physical characteristics (soil porosity and specific gravity) and Total Hydrocarbon Content (THC) of the soil samples were tested for, after the full acclimatization of the soil samples, and at the end of the 10 week experimental period, in accordance with standard methods. Results of the study showed that addition of the compost manure and organic soap the contaminated soil samples significantly (p ≤0.05) degraded the THC, and improved the soil physical characteristics. The result showed that the combination of compost manure and organic soap gave the best remediation result (from 957.21 mg/kg to 154.36 mg/kg), followed by organic soap (from 957.21mg/kg to 203.61 mg/kg), and then compost manure (from 957.21 mg/kg to 262.03 mg/kg). At the end of the experimental period, vegetative growth was observed in the treated soil samples; whereas, in the control soil samples vegetative growth was absent. Results obtained from this study have shown that amending petroleum products contaminated soils with compost manure and organic soap will enhance remediation of petroleum products contaminated sites.